Long-Term Monitoring of the Behavior of Modified Bitumens of RC Type - Varaus, Michal; Dašek, Ondřej; Hýzl, Petr; Stehlík, Dušan; Spiegl, Markus (MDPI, 2024)
This paper discusses the properties of OMV Starfalt® PmB 45/80 RC bituminous binder developed by the Austrian oil company OMV Downstream GmbH (OMV, Vienna, Austria), intended to be used for the recycling of reclaimed asphalt mixtures (RAP). The binder is characterized by various adjusted properties like higher needle penetration, higher softening point and higher elastic recovery (close to 95–100%), with the aim to compensate for the properties of the aged binder contained in the reclaimed asphalt. Three experimental sections were laid in the Czech Republic. Monitoring was performed on these sections (cores were taken after 0, 6, 12, 24, 44 and 93 months) with a consecutive analysis of the properties of the used binder—the binder was extracted from the cores and tested for penetration, softening point, critical temperature at bending beam rheometer (BBR), complex modulus and phase angle using a dynamic shear rheometer (DSR). The previously described binder was used during the construction of trial sections in the villages Domasov and Lednice and near the city Opava. In the first case, a surface course mixture of asphalt concrete type (AC surf 11+) contained 18% of RAP, whereas in the second and third case, a binder course mixture of asphalt concrete type (AC bin 22 S) comprised 23% and 39% of RAP, respectively. After approx. 8 years (Domasov and Lednice) and 3.5 years (Opava) in service, no failures or defects were recorded at any of the sections. This paper gives an update of the research work carried out in 2019 with the latest results from 2023.

This paper discusses the properties of OMV Starfalt® PmB 45/80 RC bituminous binder developed by the Austrian oil company OMV Downstream GmbH (OMV, Vienna, Austria), intended to be used for the recycling of reclaimed asphalt mixtures (RAP). The binder is characterized by various adjusted properties like higher needle penetration, higher softening point and higher elastic recovery (close to 95–100%), with the aim to compensate for the properties of the aged binder contained in the reclaimed asphalt. Three experimental sections were laid in the Czech Republic. Monitoring was performed on these sections (cores were taken after 0, 6, 12, 24, 44 and 93 months) with a consecutive analysis of the properties of the used binder—the binder was extracted from the cores and tested for penetration, softening point, critical temperature at bending beam rheometer (BBR), complex modulus and phase angle using a dynamic shear rheometer (DSR). The previously described binder was used during the construction of trial sections in the villages Domasov and Lednice and near the city Opava. In the first case, a surface course mixture of asphalt concrete type (AC surf 11+) contained 18% of RAP, whereas in the second and third case, a binder course mixture of asphalt concrete type (AC bin 22 S) comprised 23% and 39% of RAP, respectively. After approx. 8 years (Domasov and Lednice) and 3.5 years (Opava) in service, no failures or defects were recorded at any of the sections. This paper gives an update of the research work carried out in 2019 with the latest results from 2023.
Long-Term Monitoring of the Behavior of Modified Bitumens of RC Type
Keywords: Asphalt mixture; polymer modified bitumen; PMB RC; reclaimed asphalt; reclaimed asphalt pavement; test section; Asphalt mixture; polymer modified bitumen; PMB RC; reclaimed asphalt; reclaimed asphalt pavement; test section